Karyotype study on pseudoscorpions of the genus Lasiochernes Beier (Pseudoscorpiones, Chernetidae) - Stáhlavský, Frantisek; Henderickx, Hans; Král, Jirí (Folia biologica, 2005)
Karyotypes of the genus Lasiochernes (Pseudoscorpiones, Chernetidae) are studied for the first time. The diploid chromosome numbers of males were found to be 2n = 61 in L. pilosus, 2n = 69 in L. siculus and 2n = 73 in L. cretonatus. Karyotypes of all species mainly consist of biarmed chromosomes; the sex chromosome system is XO. Remarkably, the X chromosome displays partial (L. cretonatus), or even total (L. pilosus), negative heteropycnosis during the spermatogonial metaphase.
Keywords: Animals; Karyotyping; štíři; zvířata; karyotypizace; Scorpions